Freezing under electrical and magnetic disturbances; A review - LeBail, Alain; Xanthakis, Epameinondas; Havet, Michel (My University, 2015)
Phase change in biological tissues may be affected by electrical and magnetic disturbances. This presentation proposes a review based on existing literature as well as some very recent results on freezing under static electric field and microwave conditions. Freezing under static electric field of water, aqueous solution and pork meat has been investigated by the authors, showing the ability of this process to refine ice crystals in frozen matrices. SEF permits to lower the supercooling and to trigger the phase change of water to ice. The use of radiofrequencies and microwaves has been used recently by researchers to promote refined ice crystallization in food systems. Even though the energy optimization of the process is still in debate, the benefit in terms of size of ice crystals has been evidenced.
Keywords: Freezing; Static electric; Microwave